Architecture for high data availibility using server virtualization for disaster recovery - Mohd Sahalan @ Salam, Maznifah (2015)
Data, information and knowledge are becoming the most valuable commodity in everyday business exchange and transactions. Information availability has become increasingly central to organizations’ success. Organizations have been targeted by attackers for the value of their data and information. These profound evolutions has changed and challenged the aspects of information security in ensuring organizations information are secure and be made available when needed. By using virtualization as a recovery platform, organization can protect a larger share of data center workloads without having to invest in costly duplicate hardware and software. This research proposes an architecture using server virtualization to provide high availability of data,through fast and high data through fast and high data recovery on virtual infrastructure for disaster recovery. The proposed architecture uses multi side network RAID to achieved return of time objectives (RTO) and return of point objectives (RPO) of the application in the organization. In server consolidation, multiple physical server applications are deployed onto the virtual machines (VM), which then would run on a single or fewer real high-end servers to achieve better performances compared toutilizing several or even hundreds of traditional servers. In addition, data protection becomes a big problem where the organizations are responsible to overcome the problem of data loss due either intentionally or unintentionally. Security perimeters are used in the proposed architecture to maximize the data protection in the organization. To evaluate the proposed architecture, experiments using existing tools with virtualization technologies such as VMWare, Ranger Pro for backup and Trend Micro Deep Security have been carried out. This research proposes an architecture which simulates automated data replication from production site to disaster recovery site that creates an active-active environment. The proposed architecture contributed good result in Recovery Point Objective (RPO), Recovery Time Objective (RTO), data loss and data availability at 99.91 % of data are recovered during recovery process. Recovery platform using virtualization technology can protect a larger share of disaster recovery workloads in terms of high availability and data protection.